Teaching writing skills through genre: applying the genre-based approach in Iran - Ariyanfar, Somayye; Mitchell, Rod (International research journal of management, IT and social sciences, 2020)
Developing effective argumentative and persuasive texts is a challenge for both native and non-native students of writing skills, where a lack of linguistic, rhetorical, and cultural awareness skills are major problems in effective written communication. International research results show that a Genre-Based Approach based in particular on Systemic Functional and Cognitive Linguistics allows students to take a significant leap towards controlling macro and micro-genre structures as well as language and that taking a consciousness-raising approach to genre seems to be a key contributing factor to better writing development. We report on the findings of two recent Iranian studies, one that implemented the Genre-Based Approach, and the other Mobile-Assisted Dynamic Assessment following mixed Product-Process methodology, as well as giving an overview of some recent research into the development of academic writing skills through genre teaching-learning in contrast to traditional approaches. Results show that, though traditional methodologies can have success, the Genre-Based Approach, with its focus on better genre characteristics identification along with improved teaching and learning methodology, combining elements of structure, language, rhetoric, and cultural contextualization, gives more rapid results, and leads to better and more confident writers, as well as better syllabus development.